Pengaruh Manajemen Praktik Kerja Lapangan dan Bursa Kerja terhadap Kesiapan Kerja Siswa SMK Bangka Barat - Rina Maya Sari; Syarwani Ahmad; Nurlina, Nurlina (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study aims to analyze the influence of Field Work Practice (PKL) management and Special Job Exchange (BKK) management on the work readiness of vocational high school students in West Bangka Regency. This research employed a quantitative approach using a survey method. The population consisted of twelfth-grade vocational high school students in West Bangka Regency, with samples determined through proportional random sampling. The research instrument was a questionnaire that had been tested for validity and reliability. Data were analyzed using multiple linear regression to determine both partial and simultaneous effects among variables. The results indicate that PKL management has a positive and significant effect on students’ work readiness. Likewise, BKK management also shows a positive and significant influence on work readiness. Simultaneously, both variables significantly contribute to improving students’ readiness to enter the workforce. Effective PKL management, including proper planning, implementation, and evaluation, along with well-managed BKK services that provide job information and employment access, enhances students’ competencies, professional attitudes, and self-confidence. Therefore, optimizing PKL and BKK management is an important strategy to improve the quality of vocational high school graduates who are ready for employment.